D-Pare Model as an Educational Media in Improving Behavior Prevention of Dental and Oral Diseases in Adolescents - Muh. Firdaus Tullah; Bedjo Santoso; Rappi Rappi (Journal Research of Social Science, Economics, and Management, 2022)
Dental health is integral part of general health. According to RISKESDAS in 2018, based on age, the proportion of caries aged 5-9 years is 67.3% and age 10-14 years is 55.6%. Various dental health service programs continue to be developed to reduce dental and oral health problems, including by improving the quality of the media used. The relevant media used today is technology-based media. Producing augmented reality models as a medium of education in improving dental and oral disease prevention behaviors in adolescents. This type of research is a mix method. The method used is Research and Development and the research design used is quasy experiment Pretest-Posttest group design. Variables in this study: Knowledge, attitudes, actions and debris index. The research project was 2 groups: Intervention 40 people given D-Pare Model and Control 40 people given Animation media . Data tested using Wilcoxon and Mann-Whitney. The hypothesis test meaningfulness criterion uses the p-value of the delta value (?).The D-Pare model is feasible as a dental health education media with expert validation results of 87% and a p-value of 0.000 and unpaired test results stating that this application is effective in increasing knowledge (?5.33), attitude (?8.64), action (?2.70) and decreasing the debris index score (?0.587) compared to the control group. The D-Pare model proved feasible and its application was effective as an effort to improve dental and oral disease prevention behaviors and a decrease in debris index scores in adolescents compared to the control group.